ANALISIS PROMOSI PERIKLANAN TERHADAP TINGKAT PENJUALAN MOTOR YAMAHA - Nurlinasari, Nunung; Uzlifah, Siti (Universitas Wiralodra, 2022)
The purpose of this study is to analyze Advertising Promotion on Yamaha Motorcycle Sales Level at PT JG Siliwangi. The method used is descriptive descriptive analysis method, namely the research method by conducting direct observations of the object under study according to the circumstances and conditions at the time the research was conducted. The population in this study were young entrepreneurs who were under the guidance of DKOKP, totaling 58 entrepreneurs. Because the population is less than 100, the formula N = n is used). In this study, the sample was young entrepreneurs, totaling 58 people. The results show that advertising promotions have an effect on sales, which can be concluded with a simple linear regression analysis formulated into the regression equation Y=33.94+0.50 X. This equation means that if the value of X is increased by one unit, then Y will increase by 0.50 at a constant level of 33.94, so it can be concluded that if the promotion is implemented properly then the level of sales will increase. Based on the tcount value of 4.94, it is bigger than ttable which is 1.993, so the null hypothesis (Ho) is rejected and the alternative hypothesis is accepted. It can be concluded that the correlation effect (r) of 0.501 is in the medium category. So there is a moderate relationship between Advertising Promotion and Sales at PT Jayamandiri Gemasejati (JG Motor) Siliwangi Cirebon that can be proven true.